RUTA TURÍSTICA Y SU IMPORTANCIA EN EL DESARROLLO AGROTURÍSTICO DEL CANTÓN URDANETA - Posligua Peña, Maria Belen (2024)
The objective of the research is to analyze an agrotourism route in the Urdaneta canton, in order to promote the economic, social and environmental development of the area. Through a tourism inventory, the main agrotourism attractions were identified, such as the Jacome Family Cattle Ranch, the Bus Pal Farm, the Mama Cocha Spa, and the Cristal Waterfall. The proposed 18.4 km route integrates these resources strategically, offering a diverse and enriching experience for tourists. In addition, promotional strategies were designed and implemented, such as the creation of a triptych adapted for social networks, to increase the visibility of the route and attract a wider audience. The results show that the route has great potential to become a recognized agrotourism destination, provided that the infrastructure is improved, community participation is encouraged and sustainable tourism is promoted. This initiative will not only benefit visitors, but will also contribute to the integral development of the Urdaneta canton.